Sexual Harassment and Sexual Assault in Early Adulthood: National Estimates for College and Non-College Students. (September 2020) - Mumford, Elizabeth A.; Potter, Sharyn; Taylor, Bruce G.; Stapleton, Jane
Young adults are at high risk for sexual harassment and sexual assault. Although attention has been given to prevention on college campuses, the need for prevention may be at least as high for young adults who do not attend college as for young adults who do. In October 2019, we administered a nationally representative survey of 893 adults to measure sexual harassment and sexual assault victimization during a recall period defined as "during college years" for respondents who had enrolled in college at any time or "ages 18-24" for respondents not in college. Reported rates of sexual harassment (32.7%) and sexual assault (24.6%) during early adulthood were similar for respondents who reported having ever enrolled in college and for respondents who reported never attending college. Women were more likely than men to report both sexual harassment (37.4% vs 22.4%) and sexual assault (36.0% vs 16.0%) during early adulthood. Compared with respondents aged ≥30, respondents aged 18-29 were 105% more likely to report sexual harassment and 65% more likely to report sexual assault. Moreover, sexual harassment experiences predicted sexual assault victimization (adjusted odds ratio = 18.1). This study highlights the importance of attending to sexual harassment and sexual assault risks for young adults through research, policy, and criminal justice structures beyond institutions of higher education. Evidence that sexual harassment is strongly associated with sexual assault victimization of young adults highlights the importance of naming and stemming early behavioral transgressions across the US population.